Massage with virgin coconut oil as Evidence Based to reduce the incidence of pressure sores in critical patients - Andi Kurniawan; Beti Kristinawati (Caring : Jurnal Keperawatan, 2021)
Patients treated in intensive care are at high risk of decubitus due to prolonged bed rest with conditions of limited mobility and loss of consciousness. The incidence and prevalence of decubitus is one of the most representative indicators of the quality of nursing care. This study aims to determine the effectiveness of giving coconut oil massage to prevent decubitus in the Intensive Care Unit of Sukoharjo District Hospital. Problem analysis is carried out to obtain information about the effectiveness of massage using virgin coconut oil to prevent pressure sores. Massage interventions using virgin coconut oil were carried out on 7 patients treated in the ICU and were selected based on established criteria. Massage action using virgin coconut oil is done once a day for 5 days. The results obtained during the study were effective in reducing pressure sores during from very high to high. The study can be applied to patients who experience bedrest for a long time. There is an effect of skin care with massage effleurage with VCO. Pasien yang dilakukan perawatan di ruang rawat intensif beresiko tinggi mengalami decubitus karena tirah baring yang lama dengan kondisi keterbatasan gerak dan penurunan kesadaran. Insiden dan prevalensi decubitus adalah salah satu indikator yang paling representatif dari kualitas asuhan keperawatan. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian massage coconut oil untuk mencegah decubitus di Ruang Intensive Care Unit RSUD Sukoharjo. Analisis masalah dilakukan untuk mendapatkan informasi tentang efektifitas massage menggunakan virgin coconut oil untuk mencegah terjadinya dekubitus. Intervensi massage menggunakan virgin coconut oil dilakukan pada 7 orang pasien yang dirawat di ruang ICU dan dipilih berdasarkan kriteria yang telah ditetapkan. Tindakan massage menggunakan virgin coconut oil dilakukan satu kali sehari selama 5 hari. Hasil yang diperoleh selama penelitian efektif untuk menurunkan luka tekan selama dari sangat tinggi menjadi tinggi. Penelitian dapat diaplikasikan pada pasien yang mengalami bedrest dengan waktu yang lama. Ada pengaruh perawatan kulit dengan massage effleurage dengan VCO.